1987
DOI: 10.1161/01.hyp.10.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Tilt test in essential hypertension. Differential responses in heart rate and vascular resistance.

Abstract: SUMMARY Changes in hemodynamic parameters following 50-degree head-up tilt were studied in a population of 56 men, including 35 subjects with sustained essential hypertension and 21 agematched normotensive controls. The increase in heart rate following tilt was similar in both groups and exhibited the same reduction in response with age. The increase in vascular resistance following tilt was strongly and positively correlated with both age and baseline vascular resistance. The latter finding was observed mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…Therefore, it seems that hypertensive patients with greater arterial stiffness have a lesser ability to buffer against BP increases in the morning. Based on the finding that the contribution of total peripheral resistance (TPR) to BP change by orthostasis became greater, while the contribution of heart rate (HR) decreased with age in hypertensive subjects (16), the sympathetic baroreflex, which regulates BP via vasoconstriction, may play a more important role in control of morning BP in elderly hypertensive subjects. The morning surge is actually assessed with night time BP and morning BP for 2 h after waking up (12), suggesting that the morning surge includes BP rises upon standing.…”
mentioning
confidence: 99%
“…Therefore, it seems that hypertensive patients with greater arterial stiffness have a lesser ability to buffer against BP increases in the morning. Based on the finding that the contribution of total peripheral resistance (TPR) to BP change by orthostasis became greater, while the contribution of heart rate (HR) decreased with age in hypertensive subjects (16), the sympathetic baroreflex, which regulates BP via vasoconstriction, may play a more important role in control of morning BP in elderly hypertensive subjects. The morning surge is actually assessed with night time BP and morning BP for 2 h after waking up (12), suggesting that the morning surge includes BP rises upon standing.…”
mentioning
confidence: 99%
“…These findings are in agreement with previous investigations reporting that the increase in vascular resistance in response to head-up tilt was amplified in hypertensive subjects compared with NTs, and was positively correlated with age and baseline values. 36 The exaggerated vascular resistance response to head-up tilt in hypertension has not been explained by a greater sympathetic response. 37 Thus, mechanisms other than autonomic neural regulation should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…37 Thus, mechanisms other than autonomic neural regulation should be taken into consideration. London et al 36 suggested that vascular wall hypertrophy might amplify the vascular resistance responses to head-up tilt. In addition, hormonal responses to central hypovolemia could induce different vascular resistance responses.…”
Section: Discussionmentioning
confidence: 99%
“…10,[17][18][19][20] When a normal adult stands upright, 500-700 ml of blood are pooled in the legs, reducing cardiac output and arterial pressure. The fall in pressure activates baroreceptors, which then increase sympathetic outflow and inhibit parasympathetic activity, leading to vasoconstriction, increased heart rate and increased myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%